Milling process effect on the physiochemical and rheological properties of flour types resulting from Syrian wheat and their microminerals concentration (Damascus University Journal of agriculture sciences, 2022)
This research was conducted at the Central Grain Laboratory, the Ministry of Internal Trade, and the laboratories of the Department of Soil Sciences, Faculty of Agriculture, University of Damascus, with the aim of evaluating the milling process effect of local wheat types on the physiochemical and rheological properties of the resulting flour types and their microminerals content. A variety of each type of local wheat (durum wheat and soft wheat) was selected, the grains were milled to produce three types of flour with different extraction rates (72%, 80% and 100%), and the physiochemical and rheological properties of the flour were analyzed according to the AACC approved methods, and micronutrient contents were estimated using atomic absorption technology. The physiochemical properties analysis of flour showed significant differences between the types of flour for each type of wheat, and between the types of wheat. Raising the flour extraction rate significantly increased the flour color degree, ash content and quantitative protein properties, in contrast, the gluten index values decreased. On the other hand, flour water absorption, dough development time and dough weakness degree increased, and dough stability time and the valoremetric number decreased with the increase in the flour extraction rate, and it was noted decreases in the area, dough resistance to extension, maximum dough resistance to extension and dough elasticity, and the dough extensibility increased with the increase in the flour extraction rate. This study showed that a decrease in extraction rate significantly reduced the of micromineral contents in the resulting flour, and the value of the decrease changed according to flour extraction rate and the mineral type, as the concentration of micromineral in standard flour decreased by (42.84% and 41.66%) for cobalt, (41.21% and 40.51%) for manganese, (35.12% and 37.10%) for zinc, (22.16% and 21.64%) for copper and (16.55% and 18.42%) for iron, and in high quality flour by (82.44% and 81.10% ) for manganese, (77.26% and 71.32%) for cobalt, (66.05% and 67.22%) for zinc, (43.10% and 41.44%) for copper and (30.65% and 31.25%) for iron for durum and soft wheat respectively.
Keywords: Physiochemical properties; reheological properties; micromineral